GaN power IC design using the MIT virtual source GaNFET compact model with gate leakage and VT instability effect. (28th January 2021) - You, Shuzhen; Li, Xiangdong; Geens, Karen; Posthuma, Niels; Zhao, Ming; Liang, Hu; Groeseneken, Guido; Decoutere, Stefaan
Abstract: This work presents the MIT virtual source GaNFET model for GaN integrated circuit (IC) design, which is adapted to model the threshold voltage ( V T ) instability and p-GaN gate leakage. Because of the lack of GaN pFETs, the source follower topology is often implemented in GaN ICs, suffering from an instable V T drop from rail to gate. With the adapted model, the simulation successfully reproduced the evolution of the output waveforms of a monolithically integrated GaN driver circuit under switching stress. Moreover, the gate voltage redistribution of the power p-GaN gate HEMTs controlled by the integrated GaN driver is evidently proved to strongly depend on the gate leakage. If neglecting the V T shift and gate leakage, the design could induce some malfunction.